Evaluation of Internal Policy of Electronic-Based Government System (SPBE) in Pariaman City - Fitri, Ulya; Dewi Dahlan; Ihsan, Zaimul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Internal policy is an important indicator in assessing the maturity level of the implementation of the Electronic-Based Government System. In the city of Pariaman, efforts are also being made to improve the index level of the SPBE assessment by evaluating the internal policy domain, with the expectation of detecting how policies are well prepared and how these policies can serve as guidelines for the governance of SPBE in the City of Pariaman. Using Edward Suchman's evaluation theory, which consists of 6 evaluation stages: policy objectives, problem analysis, activity standardization, gap analysis, change determinants, and impact indicators. The research method is descriptive qualitative, taking samples from the most relevant informants (purposive sampling). The research results indicate that several important policies related to the architecture and roadmap of the SPBE in the City of Pariaman have not yet been prepared due to the recent formation of the coordination team. Human resources need to be improved through recruitment and by enhancing the competencies of existing staff. Furthermore, the government needs to respond promptly to the latest regulations from the central government as well as the rapidly evolving latest technology and information developments.